Who Will Save the Olive Tree?: C-443/18, Commission v Italy. (19th December 2019) - PAGANO, Mario
Abstract : In Xylella II the CJEU was called upon to assess whether Italy had failed to meet the obligations stemming from the Plant Health Directive and Decision 2015/789/EU, aiming to inhibit the spread of the plant pathogen Xylella fastidiosa in Apulia (Southern Italy). In carrying out its review, the Court relied to a large extent on the scientific evidence submitted by the Commission. It found that the Member State had failed to properly remove infected plants and monitor the presence of the pathogen in the 20km strip dividing the infected zone from the buffer zone. However, the Court also confirmed that in proceedings brought under Article 258, the burden of proof lies on the Commission, which may not rely on any presumption to demonstrate the State's failure to meet EU law obligations. The Italian authorities are now expected to comply with the Court's ruling, as financial sanctions may be imposed at a later stage.